Hubungan Dukungan Psikososial dengan Stres Pada Keluarga Orang dengan Gangguan Jiwa - Kirana, Wahyu; Anggreini, Yunita Dwi; Yousriatin, Fajar; Safitri, Dewin (STIKES Ngesti Waluyo, 2023)
Family plays an important role in caring for family members with mental disorder. Long-term care can cause stress for families caring for people with mental disorder. Families who do not have psychosocial support are prone to experiencing stress which can have an impact not only on themselves but also on the family members whom they cared for. Psychosocial support includes the use of coping strategies, namely problem-focused coping and emotion-focused coping which can help families to reduce the stress they experience. The purpose of this study was to determine the relationship between psychosocial support and stress in families who care for family member with mental disorder. The research used a correlational design with a cross-sectional approach. The population of this study was families who cared for people with mental disorder in the UPT Tanjung Hulu Health Center, Saigon Health Center and Kampung Dalam Health Center. The sampling technique in this study used purposive sampling. The instruments used were Ways of Coping and Depression, Anxiety Stress Scale. The data then analyzed using Spearman rho. The study result showed that there was a relationship between psychosocial support and stress in families who cared for people with mental disorder. Thus, it can be concluded that the higher the psychosocial support owned by families who care for people with mental disorder, the lower the stress experienced.